Hipertensi sebagai Komorbid Tunggal Merupakan Faktor Risiko Kematian COVID-19: Case-Control Study - Zenia Salha; Endang Suherlan; Heni Muflihah (UNISBA Press, 2023)
Abstract. The mortality of Coronavirus Disease 2019 (COVID-19) is associated with elderly age, gender, and comorbid hypertension. Studies examining the relationship between comorbid hypertension and COVID-19 mortality by controlling for age and gender is limited. This study aimed to analyze hypertension as a risk factor for the mortality of COVID-19 by controlling age and gender. This case-control study medical records. The subjects were confirmed COVID-19 patients who were hospitalized at dr. Slamet Garut period December 2020 – December 2021. The case group was COVID-19 patients who died following hospitalisation. The control group was survived COVID-19 patients who were individually matched with the case group in the age and sex. Comorbid hypertension is hypertension was defined as alone without other comorbidities. A total of 322 subjects consisting of 161 patients in the case group and 161 patients in the control group. In the case group, 151 patients (93.8%) were elderly people, 83 patients (51.5%) were female, and 87 patients (54%) had comorbid hypertension. Comorbid hypertension was present in 87 people (54.0%) of the case group dan 24 people (14.9%) of the control. Hypertension has a significant relationship with the mortality of COVID-19 (p=0.000) with OR 6.711. This study concludes that COVID-19 patients with hypertension as a single comorbid have a 6 times higher risk of death than patients in the same age and sex. Abstrak. Kematian Coronavirus Disease 2019 (COVID-19) berhubungan dengan usia lansia, jenis kelamin, dan komorbid hipertensi. Penelitian yang mengkaji hubungan hipertensi dengan kematian COVID-19 dengan mengendalikan faktor usia dan jenis kelamin masih jarang. Penelitian ini bertujuan menganalisis faktor resiko hipertensi pada kematian COVID-19 dengan mengendalikan usia dan jenis kelamin. Penelitian case control ini menggunakan rekam medis. Subjek penelitian adalah pasien terkonfirmasi COVID-19 yang dirawat inap di RSUD dr. Slamet Garut periode Desember 2020 – Desember 2021. Kelompok case adalah pasien COVID-19 yang meninggal. Kelompok control adalah pasien COVID-19 tidak meninggal yang sesuai usia dan jenis kelamin pada setiap subjek (individual matched) kelompok case. Komorbid hipertensi didefinisikan penyakit hipertensi saja tanpa disertai komorbid lain. Subjek penelitian berjumlah 322 orang yang terdiri dari 161 kelompok case dan 161 kelompok control. Pasien COVID-19 meninggal berusia lansia sebanyak 151 orang (93.8%), perempuan 83 orang (51.5%) dan memiliki komorbid hipertensi 87 orang (54%). Komorbid hipertensi pada kelompok case sebanyak 87 orang (54.0%), sedangkan kelompok control 24 orang (14.9%). Hipertensi memiliki hubungan dengan kematian COVID-19 secara signifikan (p=0.000) dengan OR 6.711. Kesimpulan penelitian ini pasien COVID-19 adalah komorbid tunggal hipertensi memiliki resiko 6 kali lebih tinggi untuk meninggal dibandingkan pasien lain pada usia dan jenis kelamin sama.